2017
DOI: 10.1016/j.rboe.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Fresh osteochondral knee allografts in Brazil with a minimum two-year follow-up

Abstract: ObjectiveThe present study aimed to report the results of the first series of cases of fresh ostechondral allografts in the knee joint in Brazil with a minimum follow-up of two years.MethodsA protocol of procurement, harvesting, processing, and utilization of fresh osteochondral allografts in the knee joint was established, beginning with legislation modifications, graft harvesting techniques, immediate processing, storage of fresh grafts, and utilization of two surgical techniques of osteochondral transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…F or osteochondral defects of the knee in relatively young and active patients, FOCA is an attractive treatment option because it may postpone or eliminate the need for TKA. Although smaller, contained lesions may be treated with newer techniques such as trephined plug grafts, the use of bulk FOCA to treat large chondral defects (i.e., >3 cm) in the knee has been documented in a number of studies [9][10][11][12][22][23][24] . A systematic review of knee FOCA studies found good durability and survival in 75.0% of 291 patients at a mean of 12.3 years postoperatively 19 .…”
Section: Discussionmentioning
confidence: 99%
“…F or osteochondral defects of the knee in relatively young and active patients, FOCA is an attractive treatment option because it may postpone or eliminate the need for TKA. Although smaller, contained lesions may be treated with newer techniques such as trephined plug grafts, the use of bulk FOCA to treat large chondral defects (i.e., >3 cm) in the knee has been documented in a number of studies [9][10][11][12][22][23][24] . A systematic review of knee FOCA studies found good durability and survival in 75.0% of 291 patients at a mean of 12.3 years postoperatively 19 .…”
Section: Discussionmentioning
confidence: 99%